Performance comparison and impact of weather conditions on different photovoltaic modules in two different cities - Bahanni, Caouthar; Adar, Mustapha; Boulmrharj, Sofia; Khaidar, Mohammed; Mabrouki, Mustapha (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
This work is based on a comparative study of the impact of meteorological conditions as well as the assessment of the production performance of two identical photovoltaic stations installed in two Moroccan cities, the stations are based on three different technologies. The measures of one year of operation from January 2017 to December 2017 were evaluated. The annual average performance ratios were found to be 82.42%, 79.99% and 78.74% in Beni Mellal, and 85.29%, 84.61% and 70.41% in El Jadida for the polycrystalline (pc-Si), monocrystalline (mc-Si), and amorphous (a-Si) respectively. The photovoltaic efficiency was calculated at 12.24%, 11.89%, and 11.71% in Beni Mellal; and 12.59%, 12.49%, and 10.42% in El Jadida by the same order. Statistical analysis was carried out to establish the correlation with photovoltaic (PV) production showed that after irradiation, the temperature is the most influencing meteorological factor for PV production, revealing a degradation in the performance ratio of 2.5%, 2%, and 1% for each increase of 8 °C in temperature for monocrystalline, polycrystalline and amorphous technologies respectively at Beni Mellal. While at El Jadida the reduction in the performance ratio is evaluated by 5.5%, 5.2%, and 3% for each 8 °C increase in temperature for the same order.